Age-Related Alterations of the Macular Choroid in Healthy Eyes Assessed by Swept-Source Optical Coherence Tomography Angiography - Verma, Aditya (Ophthalmic surgery, lasers & imaging retina, 2023)
OBJECTIVE: To analyze age-related changes in the choroid in healthy eyes using swept-source optical coherence tomography angiography (SS-OCTA)